Electric Control and Meterological Validation of Sensors in Dynamic Metering System of Fluids - Abdelkader Harrouz; Omar Harrouz; Ali Benatiallah (Institute of Advanced Engineering and Science, 2013)
The verification method of a metering system varies from one site to another, depending on the available equipment and the calibration equipment measuring instruments installed. However, the effectiveness of the verification and control (primary or periodic) requires a good control system and calibration process. This paper focuses on the errors of measuring instruments in a dynamic system of metering fluids and respect of the tolerance defined by the international standards and recommendations. In a first step, we describe the experimental methodology adopted for evaluating the effectiveness of different systems Dynamic count. Next we will compare the results of measurements between the simulated values and the values read from the computer. Finally, we conclude on the validity of the instruments according to the errors identified and the errors.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4979